Design, Formulation, and Optimization of Novel Mouth Dissolving Tablet of Drug Ketorolac Using Special Super Disintegrate - Khare, Ekta (Asian Journal of Pharmaceutics (AJP), 2022)
Background: Due to its versatility and convenience, the orally disintegrating tablet is the most advanced type of oral solid dosage form. Compared to traditional tablets, it dissolves in the oral cavity within 1 min of contact with saliva, increasing the effectiveness of the active pharmaceutical ingredient without chewing, and without the need for water for administration. Materials and Methods: Oral soluble ketorolac tromethamine tablets have been prepared by direct compression using various superdegradants such as crospovidone, croscarmellose sodium, and sodium starch glycolate at different concentrations. The manufactured tablets are evaluated for hardness, crushability, weight change, breakdown time, wetting time, and drug release in vitro. Results and Conclusion: Study results before compression and after compression for all formulations are within standard limits. All batches of tablets were found to release more than 80% of the drug within 5 min. The desired quality of the tablets disintegrates in the mouth and contributes to a faster absorption of the drug and a rapid onset of the therapeutic effect.